HUBUNGAN KARAKTERISTIK LANJUT USIA DENGAN ACTIVITY OF DAILY LIVING DI DESA SILANTOMJULU - Julia Mahdalena Siahaan; Kesaktian Manurung; Yunida Octavia Turisna (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Elderly individuals experience a variety of health issues that require quick and comprehensive management. The bodies of elderly people become less effective as they age, both physically and psychologically. This study aims to explore the relationship between aging characteristics and Activities of Daily Living (ADL) in Silantom Julu Village, Pangaribuan District, North Tapanuli Regency in 2023. This research is quantitative and employs a survey method with a cross-sectional research design. The research was conducted in March - May 2023. The study population consisted of 58 participants, all of whom were sampled using the total population technique. Data analysis was performed using the Chi-Square test. The results showed that the majority of the elderly individuals aged 60-74 accounted for 48 people (82.8%). Additionally, the majority of the elderly were male, totaling 32 people (55.2%). Furthermore, the majority of the elderly individuals were employed, amounting to 48 people (82.8%). About 35 people (60.3%) of the elderly lived with their families, and approximately 40 people (69.0%) were diagnosed with illnesses. The majority of respondents demonstrated issues with Activities of Daily Living. The statistical analysis results indicate that the respondents' age (p-value 0.000), occupation (p-value 0.003), and disease diagnosis (p-value 0.020) are correlated with Activities of Daily Living. However, gender (p-value 0.078) and residence status (p-value 0.462) showed no relationship with Activities of Daily Living. It is recommended that health agencies continue to implement 'posyandu' programs for the elderly, as they are effective in early disease detection.